2017
DOI: 10.1097/mnm.0000000000000640
|View full text |Cite
|
Sign up to set email alerts
|

Higher preablative serum thyroid-stimulating hormone level predicts radioiodine ablation effectiveness in patients with differentiated thyroid carcinoma

Abstract: Higher preablative serum TSH predicts a better rate of ablation in patients with differentiated thyroid cancer treated with I after thyroidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Whereas the patients in the 60 ≤ TSH < 90 subgroup took the lowest dose of L-T 4 among the three subgroups, this indicated that the postoperative L-T 4 dose was not the only key factor for the withdrawal time. Most of the remaining clinical features were similar among the three subgroups and there was no statistical significance on therapeutic effects six months after the first 131 I treatment, which was inconsistent with the studies mentioned above (4,5). We then merged the three subgroups into the TSH ≥ 30 group.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Whereas the patients in the 60 ≤ TSH < 90 subgroup took the lowest dose of L-T 4 among the three subgroups, this indicated that the postoperative L-T 4 dose was not the only key factor for the withdrawal time. Most of the remaining clinical features were similar among the three subgroups and there was no statistical significance on therapeutic effects six months after the first 131 I treatment, which was inconsistent with the studies mentioned above (4,5). We then merged the three subgroups into the TSH ≥ 30 group.…”
Section: Discussionmentioning
confidence: 77%
“…Some researchers believed that a TSH of > 30 mU/l or THW over two weeks was not in itself required for successful 131 I treatment (6, 7). On the contrary, others suggested that DTC patients might achieve a better response to 131 I treatment after a stronger TSH stimulation level due to a probable higher 131 I uptake (4,5).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…published a report on patients who received ablation with TSH <30, with the same ablation outcome ( 44 ). On the other hand, some authors advocate the use of higher TSH values, suggesting them to be connected with better treatment outcome ( 45 , 46 ). In our two previous studies, no differences were observed comparing TSH levels and the ablation outcome ( 47 , 48 ).…”
Section: Cut-off Tsh Threshold Of 30 Miu/lmentioning
confidence: 99%
“…Therefore, it is critical to identify the predictors for the response to therapy. Previous studies showed some clinicopathological features (e.g., sex, tumor size, lymphovascular invasion, number of metastatic lymph nodes [LNs], ratio of metastatic to examined LNs [LNR], extranodal extension, and preablative-stimulated thyroglobulin [Ps-Tg]) may affect the response to therapy (5)(6)(7)(8)(9)(10)(11). However, these results are based on retrospective single-center studies, and some of them are inconsistent.…”
Section: Introductionmentioning
confidence: 99%